Metformin degradation with combined Ozone/UV/H2O2 process - Fujinami, Shoko Carissa (Nanyang Technological University, 2020)
Metformin is a commonly used drug to treat Type 2 diabetic patients. As the number of diabetic patients globally has increased from 108 million in 1980 to 422 million in 2014, it can be seen that diabetes is a common form of illness and in Singapore, there is about 1 in 10 people suffering from diabetes (Lai, 2015). Hence, there is a huge amount of intake of Metformin by diabetic patients. As our bodies are unable to fully metabolise all Metformin, a significant amount of Metformin is excreted unchanged into water bodies and studies have found that Metformin is an endocrine disruptor compound (EDC) which can interfere with reproduction system. As it is non-biodegradable, it can lead to bioaccumulation which then leads to biomagnification when the concentration of Metformin increases along the food chain, causing harmful effects to human health and the environment. Therefore, there is a need to treat Metformin in wastewater and/or water treatment plants. There are several methods available to treat Metformin such as UV oxidation, ozone oxidation, hydrogen peroxide oxidation or Advanced Oxidation Process (AOP) (Singh, Borthakur, Mishra & Tiwary, 2019). In this study, the degradation of Metformin has been investigated by a combined ozone, ultraviolet (UV) and hydrogen peroxide AOP where Ultraviolet-visible Spectroscopy (UV-Vis) instrument is being used to evaluate the degradation rate of Metformin. The effect of Metformin concentration, ozone feed rate, Hydrogen peroxide concentration, pH level and UV lamp intensity on the degradation rate of Metformin are carried out to elucidate optimal parameters. The experiments are carried out by varying one of the parameters at a time while ensuring the rest of the parameters are constant. Increasing Metformin concentration slows down the degradation rate due to an increase in number of Metformin molecules to be degraded by the same amount of hydroxyl radicals (Hofman-Caris, Harmsen & Wols, 2015). Increasing ozone feed rate has a significant impact on Metformin degradation as it can completely remove Metformin within 10 minutes at ozone feed rate of 100mg/h. An increase in ozone feed rate leads to an increase in amount of ozone molecules to undergo photolysis under UV light. Hence, more hydroxyl radicals can be formed to degrade Metformin at a faster rate. When the pH level of the solution increases, the environment becomes more alkaline. An alkaline environment has shown to increase the rate of Metformin degradation. This is because formation of hydroperoxyl anion (HO2-) is favourable in alkaline environment which then increases the rate of formation of hydroxyl radicals. HO2- also causes decomposition of hydrogen peroxide into hydroxyl radicals. As pH increases, the amount of hydroxyl radicals formed increases and hence the rate of Metformin degradation increases. Increasing lamp intensity also increases the rate of Metformin degradation. UV light acts as a catalysis for the photolysis of ozone and hydrogen peroxide into hydroxyl radicals. Thus, the increase in intensity means that there is an increase in rate of formation of hydroxyl radicals. Hence, more hydroxyl radicals are present to degrade Metformin at a faster rate. Increasing concentration of hydrogen peroxide leads to faster degradation of Metformin. As Hydrogen peroxide can undergo photolysis under UV light influence to form 2 hydroxyl radicals, more hydroxyl radicals are formed to degrade Metformin at a faster rate. This rate of degradation is also higher compared to that of increasing ozone feed rate. However, it is found that only when the concentration of Hydrogen peroxide is more than 150ppm will it show significant effect. The optimum parameters for Metformin removal are observed with Metformin concentration at 4mg/l, ozone feed rate at 100mg/h, pH level of 7, UV lamp intensity of 7W and 250mg/l of hydrogen peroxide.